2008
DOI: 10.1007/s10620-008-0388-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Results of Computed-Tomography-Guided Transcatheter Arterial Chemoembolization for Local Recurrence of Hepatocellular Carcinoma After Initial Transcatheter Arterial Chemoembolization: The Results of 85 Recurrent Tumors in 35 Patients

Abstract: The aim of this study was to retrospectively evaluate the long-term results of transcatheter arterial chemoembolization (TACE) for the treatment of local recurrence of hepatocellular carcinoma (HCC) after the first TACE. Between September 1992 and October 2004, 85 recurrent HCC nodules of 35 patients were treated by TACE. During the median follow-up period of 15.5 months (range 1.9-58.6 months), 58 of the 85 treated tumors developed local recurrence again after the second TACE. The overall 6-, 12-, and 36-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the current study, the 1‐, 3‐ and 5‐year recurrence rates of HCC following CR by TACE were 21%, 68% and 81%, respectively, and the rates in the RFA group were 26%, 56% and 74%, respectively. Also, in the previous studies, the cumulative 1‐, 2‐ and 3‐year recurrence rates have been reported to be 23–32%, 55–63% and 67–84%, respectively, in HCC patients with CR by TACE, and the cumulative recurrence rates following CR by RFA were 35–42%, 46–72% and 63–80%, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…In the current study, the 1‐, 3‐ and 5‐year recurrence rates of HCC following CR by TACE were 21%, 68% and 81%, respectively, and the rates in the RFA group were 26%, 56% and 74%, respectively. Also, in the previous studies, the cumulative 1‐, 2‐ and 3‐year recurrence rates have been reported to be 23–32%, 55–63% and 67–84%, respectively, in HCC patients with CR by TACE, and the cumulative recurrence rates following CR by RFA were 35–42%, 46–72% and 63–80%, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…However, it was mostly used at a sub-subsegmental artery or a more distal artery. Third, the local tumor control rate was lower than that in previous reports (5,11,12). We think our TACE may be incomplete even though we could insert a microcatheter into a distal position.…”
Section: Discussionmentioning
confidence: 69%
“…The identification of the dorsal sector of the liver and its detailed anatomy is of primary importance for surgical practice. Segmental transcatheter arterial chemoembolization (TACE) possesses markedly stronger anticancerous effect but much less damage to liver function; hence, its long-term effectiveness excels the conventional TACE in liver cancers treatment ( 5 - 7 ). A sufficient segmental TACE of the tumor in the dorsal sector depends on the identification of feeding arteries to the segment; however, the origin of hepatic arterial blood supplying to the dorsal sector is intricate and needs further research.…”
Section: Introductionmentioning
confidence: 99%